Load transfer mechanism of novel double-layer steel-LHDCC-steel sandwich panels under punching loads. (1st January 2021) - Huang, Zhenyu; Zhao, Xiaolong; Zhang, Wei; Fu, Zhanxia; Zhou, Yingwu; Sui, Lili
Highlights: Develop a novel double-layer steel-LHDCC-steel sandwich composite panel. Report an experimental study on double-layer sandwich panels under punching loads. Establish a punching cone model to illustrate the failure mechanisms. Propose a new model considering the bond-slip effect to predict the ultimate resistance. Abstract: This study develops a novel double-layer steel-lightweight high ductility cement composite (LHDCC)-steel sandwich composite panels with hybrid shear connectors. Two interventions are included compared to the traditional single-layer steel–concrete-steel panels: (1) material intervention: using ultra lightweight high ductility cement composite; and (2) structural intervention: using double layers to replace the single layer. The experimental program tests two full-scale single-layer sandwich panels and eight full-scale double-layer sandwich panels subjected to concentrated punching load. The specimens vary with different layer numbers, shear span-to-depth ratios, steel contribution ratios, types and spacing of shear connectors, and loading areas. The effects of these parameters on the load–displacement curve and failure mode of the composite sandwich panels are discussed in detail. Compared to the single-layer sandwich panels with comparable steel contribution ratio, the double-layer sandwich panels exhibit larger ultimate resistance and residual resistance. The punching cone model is established to illustrate the failure mechanisms of the double-layer sandwich panels, the failure sequence of which follows: (1) punching shear failure of concrete; (2) punching shear fracture of top plate; and (3) punching shear fracture of middle plate. Based on corresponding failure mechanisms, this study develops analytical models, taking into account of the above parameters, to evaluate the ultimate resistance of the composite panels. The developed models provide close predictions of each peak resistance of the single- and double- layer sandwich panels, which provides reference for the design of multilayer SCS composite panels.